TRIM71 Deficiency Causes Germ Cell Loss During Mouse Embryogenesis and Is Associated With Human Male Infertility - Torres-Fernández, Lucia A.; Emich, Jana; Port, Yasmine; Mitschka, Sibylle; Wöste, Marius; Schneider, Simon; Fietz, Daniela; Oud, Manon S.; Di Persio, Sara; Neuhaus, Nina; Kliesch, Sabine; Hölzel, Michael; et al. (Frontiers in Cell and Developmental Biology, 2021)
Mutations affecting the germline can result in infertility or the generation of germ cell tumors (GCT), highlighting the need to identify and characterize the genes controlling germ cell development. The RNA-binding protein and E3 ubiquitin ligase TRIM71 is essential for embryogenesis, and its expression has been reported in GCT and adult mouse testes. To investigate the role of TRIM71 in mammalian germ cell embryonic development, we generated a germline-specific conditional Trim71 knockout mouse (cKO) using the early primordial germ cell (PGC) marker Nanos3 as a Cre-recombinase driver. cKO mice are infertile, with male mice displaying a Sertoli cell-only (SCO) phenotype which in humans is defined as a specific subtype of non-obstructive azoospermia characterized by the absence of germ cells in the seminiferous tubules. Infertility in male Trim71 cKO mice originates during embryogenesis, as the SCO phenotype was already apparent in neonatal mice. The in vitro differentiation of mouse embryonic stem cells (ESCs) into PGC-like cells (PGCLCs) revealed reduced numbers of PGCLCs in Trim71-deficient cells. Furthermore, TCam-2 cells, a human GCT-derived seminoma cell line which was used as an in vitro model for PGCs, showed proliferation defects upon TRIM71 knockdown. Additionally, in vitro growth competition assays, as well as proliferation assays with wild type and CRISPR/Cas9-generated TRIM71 mutant NCCIT cells showed that TRIM71 also promotes proliferation in this malignant GCT-derived non-seminoma cell line. Importantly, the PGC-specific markers BLIMP1 and NANOS3 were consistently downregulated in Trim71 KO PGCLCs, TRIM71 knockdown TCam-2 cells and TRIM71 mutant NCCIT cells. These data collectively support a role for TRIM71 in PGC development. Last, via exome sequencing analysis, we identified several TRIM71 variants in a cohort of infertile men, including a loss-of-function variant in a patient with an SCO phenotype. Altogether, our work reveals for the first time an association of TRIM71 deficiency with human male infertility, and uncovers further developmental roles for TRIM71 in the germline during mouse embryogenesis.